DEVELOPING STUDENTS’ LITERARY ANALYSIS SKILLS IN PRIMARY GRADES - Matchonov, Safo (SCIENCE and SOCIETY, 2026)
This article provides a scientific and methodological justification that, since literature has the status of an independent academic subject within the general secondary education system, the methodology of teaching children’s literature in primary education should also be regarded by methodologists as an independent academic discipline. The article also discusses the stages and methods of working with literary texts in primary school.